If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3n + 8) = 12n + -7 Reorder the terms: 7(8 + 3n) = 12n + -7 (8 * 7 + 3n * 7) = 12n + -7 (56 + 21n) = 12n + -7 Reorder the terms: 56 + 21n = -7 + 12n Solving 56 + 21n = -7 + 12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12n' to each side of the equation. 56 + 21n + -12n = -7 + 12n + -12n Combine like terms: 21n + -12n = 9n 56 + 9n = -7 + 12n + -12n Combine like terms: 12n + -12n = 0 56 + 9n = -7 + 0 56 + 9n = -7 Add '-56' to each side of the equation. 56 + -56 + 9n = -7 + -56 Combine like terms: 56 + -56 = 0 0 + 9n = -7 + -56 9n = -7 + -56 Combine like terms: -7 + -56 = -63 9n = -63 Divide each side by '9'. n = -7 Simplifying n = -7
| 2(4x+5)=2x-8 | | 6(x+8)=5(x-9)+x | | m^2=25 | | -x^2+6x+135=0 | | 3(8a+5)+6(a+8)=33 | | 9e-14=9e-14 | | x^2=7x+44 | | -2=2(x-1)+6x | | 8x^2+18x-5x=0 | | -8(3-3p)-3(6+5p)=21 | | X-74=146 | | 3x^2=36-3x | | x^2+10=7x | | 2s+(7s-18)=90 | | 3z+2[2+3(z-1)]=2(3z+4) | | .2x+3=-.8 | | 4(7-4x)=4(2x+2) | | 15x+20y=575 | | 4k^2-k-3=0 | | 6x+3+5x+7=10x+4 | | 2(x-1)=0.5 | | 20x+15y=575 | | -17=-3(7+2n)+4 | | -5y+5=-6y+8 | | 3(x+5)=2x-5 | | n^2-8n+33=3+3n | | 4(7x-2)+3(16-5x)-4(3x+5)=-19 | | 5x-3=8x+9 | | -6+2x-5=5x+10-3 | | -4b(4b+4)+(17b-5)=0 | | a^2+11a-42=0 | | v^2-2v-32=-8 |